The interplay between sharing behavior and beliefs about others in children during dictator games (2018)
Previous studies in adults demonstrated that beliefs and sharing decisions in social scenarios are closely related. However, to date, little is known about the development of this relationship in children. By using a modified dictator game, we assessed sh